Genetic variability and biodiversity of Ukrainian Gray cattle by the BoLA-DRB3 gene - T. M. Suprovych; M. P. Suprovych; N. B. Mokhnachova; O. D. Biriukova; L. V. Strojanovska; V. A. Chepurna (Regulatory Mechanisms in Biosystems, 2021)
At the current stage of genetic studies of cattle, more and more attention is being drawn to autochthonous breeds. Native cattle have a number of prominent phenotypic traits and have preserved unique genes and their combinations lost by modern commercial breeds, which would be valuable to use in selective programs. We surveyed polymorphism of the Ukrainian autochthonous Gray breed according to alleles of exon 2 of the BoLA-DRB3 gene. The uniqueness of the gene lies in the broad variability of its allele variants. Significant informativeness at DNA level is quite important for genetic studies. We surveyed allele polymorphism using the PCR-RLFP method on DNA isolated from 88 samples of blood of cows and 5 samples of sperm. We identified 28 alleles, of which 23 variants were nomenclature ones and 5 (jba, *jab, *jbb, *nad and *nda) were “without established nomenclature”, their share accounting for 8.9%. Four alleles *06, *12, *16 and *jba had a frequency above 5% and occupied 69.9% of the breed’s allele fund overall. The commonest allele was BoLA-DRB3.2*16 (44.1%). In total, we found 40 genotypes. Considering the significant dominance of variant *16, as expected, 5 genotypes with its inclusion occurred: *16/*16, *12/*16, *06/*16, *16/*24 and *jba/*16. It was present in the genotype of two out three studied animals. Parameters of heterozygosity, effective number of alleles, Shannon and Pielou indices indicate that Ukrainian Gray cattle are characterized by lowest level of genetic variability and biodiversity according to the BoLA-DRB3 gene compared with other breeds. Due to significant dominance of allele *16, the breed has no inbred motifs. We noted deviation toward increase in homozygosity without deviations from the norm of the distribution according to Hardy-Weinberg equilibrium. The obtained results will be used for genetic-populational programs with the purpose of improving the genetic potential of cattle breeds in terms of economically beneficial traits and diseases of cattle.